Template Selection during Manipulation of Complex Mixtures by PCR - D.H.-F. Teng; F. Hsu; I. Peterson; K.E. Cardon; G. Caponigro; A. Kamb (BioTechniques)
PCR is ubiquitous in molecular biology. It is used to amplify single sequences from large genomes, or populations of sequences from complex mixtures such as cDNA libraries in mammalian cells. These cDNA libraries are often employed in subsequent labor-intensive experiments such as genetic screens, the outcome of which depends on library quality. The use of PCR to amplify diverse sequence populations raises important technical issues. One question is whether or not PCR is capable of maintaining population diversity, specifically with respect to template selection in the first rounds of the amplification process (i.e., the possibility that rare sequences in a complex mixture are lost because of amplification failure at the outset of the PCR). Here, we analyze the properties of PCR in the context of template selection in complex mixtures and show that it is an excellent method for preserving diversity.